O conceito assunto na arquivística: uma reflexão em arquivos permanentes a partir do evento - I soggetti e altri apparati di indicizzazione in archivistica: ipotesi di lavoro - Monção, Jane Lessa [UNESP] (2006)
Searching to concur for the construction of an intellectual device that can perfect the archival doing in the post modern world which the fierce information is optimized, to investigate itself as the notion of Subject comes being boarded in Archival literature, it aimed to offer subsidies for the eventual delimitation of the theoretician-practical field of the notion of Subject and, through the revision of pertinent literature to show the different contexts, by which the notion of Subject is lodged. For in such a way, initially it was proceeded to the revision of Archival literature, attempting for the passage, delimited for the classic tradition, of the concept of the Archival document until what the scholars of the Archival call of phenomenon of the Information. In one second stage, it was realized fullfilled revision of Archival literature, from the identification of the different boardings on the Subject in Archives. Finally it analyzes the main ones of the archival event I soggetti and altri apparati di indicizzazione in: ipotesi di lavoro, which the notion of Subject finds the biggest academic notoriety. From this way, it is proceeded the analysis of the deriving theoretical referencial of the event from two categories of analysis: concept and function of the Subject in the Archival in order to reflect on the conceptual construction of the subject in archives.